2005
DOI: 10.1186/1465-9921-6-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of serum SARS-Coronavirus IgG, pulmonary function and radiography in patients recovering from SARS after hospital discharge

Abstract: Objective: The intent of this study was to examine the recovery of individuals who had been hospitalized for severe acute respiratory syndrome (SARS) in the year following their discharge from the hospital. Parameters studied included serum levels of SARS coronavirus (SARS-CoV) IgG antibody, tests of lung function, and imaging data to evaluate changes in lung fibrosis. In addition, we explored the incidence of femoral head necrosis in some of the individuals recovering from SARS. Methods:The subjects of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
86
1
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 7 publications
8
86
1
9
Order By: Relevance
“…The serial results suggest an increase of the intra-alveolar diffusion pathway, which might be the result of diffuse alveolar damage and/or BOOP initially, 38 -41 followed by postinflammatory changes such as atelectasis, ongoing alveolitis, and parenchymal fibrosis later in the course of the disease. Our results are similar to a long-term follow-up study 44 in Beijing that reported that 27.3% of their SARS survivors (85 of 311 patients) had impaired Dlco, whereas 21.5% exhibited radiographic evidence of lung fibrotic changes at 1 year. Several studies [45][46][47] on ARDS survivors have shown that their pulmonary function generally returns to normal or near normal by 6 to 12 months, but Dlco may remain abnormal in up to 80% of patients at 1 year after recovery.…”
Section: Discussionsupporting
confidence: 89%
“…The serial results suggest an increase of the intra-alveolar diffusion pathway, which might be the result of diffuse alveolar damage and/or BOOP initially, 38 -41 followed by postinflammatory changes such as atelectasis, ongoing alveolitis, and parenchymal fibrosis later in the course of the disease. Our results are similar to a long-term follow-up study 44 in Beijing that reported that 27.3% of their SARS survivors (85 of 311 patients) had impaired Dlco, whereas 21.5% exhibited radiographic evidence of lung fibrotic changes at 1 year. Several studies [45][46][47] on ARDS survivors have shown that their pulmonary function generally returns to normal or near normal by 6 to 12 months, but Dlco may remain abnormal in up to 80% of patients at 1 year after recovery.…”
Section: Discussionsupporting
confidence: 89%
“…19 In survivors of severe acute respiratory syndrome (SARS) followed for 1 year, marked improvements in pulmonary fi brosis have been seen, but some patients still had residual changes. 20 Because this kind of fi brosis was reversible, it has been suggested that these fi ndings were partially caused by postinflammatory atelectasis rather than by genuine fi brosis alone. 21 The resolution of lung abnormalities in patients with A(H1N1) viral pneumonia seemed better than that seen in patients with SARS and infl uenza A(H5N1) infection.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] As SARS is a disease that has recently emerged, the long-term sequelae are largely unclear. Studies on the lung function outcome of SARS survivors have been reported; [9][10][11][12][13][14][15][16][17][18][19] however, the longest duration of follow up was around 3 years and small numbers of subjects were studied. 18,19 We have previously reported the 6 month 12 and 1 year outcomes 13 from the Prince of Wales Hospital SARS patient cohort, based on the available normative lung function data collected in the 1960s.…”
Section: Introductionmentioning
confidence: 99%